BCM-2.0 – The new version of computer code “Basic Channeling with Mathematica©”; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 402 - Abdrachitov S. V. Sergey Vladimirovich; Bogdanov O. V. Oleg Viktorovich; Korotchenko K. B. Konstantin Borisovich; Pivovarov Yu. L. Yury Leonidovich; Fiks E. I. Elena Ivanovna; Tukhfatullin T. A. Timur Ahatovich; Eykhorn Yu. L. Yury Leonidovich (2017, 2017)
Title screen